Analisis Kerentanan Keuangan Badan Layanan Umum Tahun 2012 - 2014 - Syahri Azda Putra; Muliadi Widjaja (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2017)
The aim of this study was to analyse financial vulnerability at the Semi Autonomous Agency (SAA) and to investigate its signs of vulnerability, whether SAA has a sound of financial conditions and to evaluate the performance of existing SAA. Based on the research findings of the 128 SAA, there were 13 SAA experiencing financial vulnerability. Variables which influence the financial vulnerability were EQUITY, ADMIN, and MARGIN. This research was conducted using a logit regression. The study recommends analysis of financial vulnerability as one of assessing criterion for measuring performance of SAA, which mainly use financial performance indicators, a part of financial indicators which already been used as promulgated in Treasury Regulation Number PER-36/NT/2012. In addition, other recommendation is to monitor intensively on SAA which experiencing financial vulnerability, and the need for periodic evaluation to measure the feasibility of SAA. The periodic evaluation can be done every two years, where definition mentioned that vulnerability in place when SAA experiencing financial vulnerability for two consecutive years. Abstrak Penelitian ini bertujuan untuk menganalisis kerentanan keuangan pada Badan Layanan Umum (BLU) dan tanda-tanda yang menunjukkan kerentanan keuangan tersebut, apakah benar-benar berkinerja baik serta untuk mengevaluasi kinerja BLU yang ada. Berdasarkan hasil pengujian kepada 128 BLU, terdapat 13 BLU yang mengalami kerentanan keuangan. Variabel yang berpengaruh terhadap kerentanan keuangan adalah EQUITY, ADMIN, dan MARGIN. Penelitian ini dilakukan dengan menggunakan metode regresi logit. Hasil studi ini merekomendasikan analisis kerentanan keuangan dimasukan sebagai salah satu cara dalam menilai kinerja BLU, terutama kinerja keuangan selain rasio keuangan yang telah digunakan saat ini dalam Perdirjen Perbendaharaan Nomor PER-36/PB/2012. Selain itu, rekomendasi berikutnya adalah melakukan monitoring yang intensif terhadap BLU yang mengalami kerentanan keuangan, dan perlu adanya evaluasi berkala untuk menentukan kelayakan suatu BLU. Evaluasi dapat dilakukan setiap dua tahun, sesuai dengan definisi kerentanan keuangan, yaitu mengalami kerentanan keuangan selama dua tahun berturut-turut.